PENGEMBANGAN MODEL ALAT STICK HOCKEY UNTUK LATIHAN PEMAIN PEMULA HOCKEY - In'am Attaqi; Uen Hartiwan; Imam Santosa CWW (Universitas Negeri Semarang, 2016)
Background issues that hamper the development of hockey in Central Java due to the lack of means of stick that is expensive and so difficult to get it. The focus of this research problem is to design products hockey stick model development tool for training novice players and test products hockey stick model development tool for training novice players.The approach used in this research is the Research and Development. Phase of the study include preliminary research, design modeling, model development testing procedures, expert Judgment, small-scale trials, trials broad scale. The subject of this study is Mts Miftahussalam 1 Wonosalam Demak. Hockey expert of experts and specialists timber expert. The data analysis phase of field work and data analysis stage include observation, observation, interviews, documentation and effectiveness testing of products, expert judgment hockey expert of experts and specialists timber expert.The results of this study are the product hockey stick for beginner hockey players training in Mts Miftahussalam 1 Wonosalam.PANDAWA hockey stick product can be used as a means of practicing basic techniques for beginner hockey players, hockey stick PANDAWA product can be used as a training tool in improving the ability of the basic techniques of playing hockey, hockey stick PANDAWA product can be used as a means of playing hockey for the novice player.